Manufacturing and services in Italian labour market areas in an historical perspective (1981-1996) - Giovanni Barbieri; Sandro Cruciani (European Regional Science Association (ERSA), 2001)
The basic hypothesis of this paper is the existence of strong territorial disparities in services development. In many areas a strict integration emerges between manufacturing production and endowment of tertiary functions; in other regions the sparse presence of services may result in belated development or slow growth. From a sectoral point of view, the analysis goes beyond the classical tripartition of industries, proposing a classification of services based both on the nature of the service given and the features of their users. From a geographical point of view, a territorial grid based on local labour market areas as proposed by Istat [1997] is adopted. The long-term analysis - based on Census data from 1981 to 1996 - allows to identify territorial regularities in development patterns across LLMAs, with respect to manufacturing and services and to different growth paths (convergence, externalisation, integration, ...).
Keywords: 330